'Restaurant reviews aren't what they used to be': digital disruption and the transformation of the role of the food critic. Issue 3 (3rd July 2018) - Kobez, Morag
ABSTRACT: This study uses data collected from interviews with professional food critics to analyse how the proliferation of amateur blog and online consumer reviews has disrupted and transformed the tenets of mainstream media restaurant reviewing. The article argues that the proliferation of digital platforms has fundamentally changed the practices of the professional restaurant critic – including changes to the process of carrying out reviews, the ethical framework guiding this process, and the format of reviews. Professional restaurant critics have been forced to accommodate to the new pressures brought by digital media. These changes mark the discursive terrain of a struggle between professional restaurant critics defending their position and status as cultural intermediaries in the gastronomic field against the entry of amateur digital competitors.